Agronomic Traits in Durum Wheat Germplasm Possessing Puroindoline Genes. (1st May 2019) - Kiszonas, A. M.; Higginbotham, R.; Chen, X. M.; Garland-Campbell, K.; Bosque-Pérez, N. A.; Pumphrey, M.; Rouse, M. N.; Hole, D.; Wen, N.; Morris, C. F.
Abstract : Core Ideas: Durum wheat is an underutilized crop due to it hard kernel texture; soft kernel durum removes this limitation. Initial soft kernel durum lines show favorable agronomic performance, including grain yield and pest resistance. Soft durum lines show strong potential for future growth in the Pacific Northwest. ABSTRACT: Durum wheat ( Triticum turgidum subsp. durum ) represents only 5% of global wheat production. Durum production is limited by its very hard kernel texture, which requires specialized milling and limits end‐product utilization. However, soft kernel durum wheat was recently developed to remove these constraints, but it has not until now been examined for its agronomic potential and pest resistance, which were the focus of this study. The soft durum lines were compared with two commercial hard red spring wheat varieties, Buck Pronto and Alum. Soft durum lines were relatively competitive for grain yield (i.e., >90%) with Buck Pronto at 16 of 34 locations. Increasing seeding rate did not increase grain yield of soft durum. The soft durum lines showed no tolerance of acid soils/Al, but exhibited moderate‐to‐strong resistance to stripe rust (caused by Puccinia striiformis f. sp. tritici ). Good resistance to stem rust (caused by Puccinia graminis f. sp. tritici ) and near complete resistance to dwarf bunt (caused by Tilletia controversa ) were observed. Resistance to Hessian fly ( Mayetiola destructor ) was observed in some of the plants, with three of the durum lines showing a larger proportion of resistant plants. Varying levels of resistance to cereal cyst nematode ( Heteroderma filipjevi ) were recorded, with some lines highly resistant. These studies show that there is good agronomic potential in the current soft durum lines for moderate yield and good pest resistance. Further breeding efforts and germplasm introgression will likely improve the competitiveness of soft durum wheat with currently grown hard red spring wheat.